2017
DOI: 10.1186/s12891-017-1532-2
|View full text |Cite
|
Sign up to set email alerts
|

Return to sports after plate fixation of humeral head fractures 65 cases with minimum 24-month follow-up

Abstract: BackgroundHumeral head fractures requiring surgical intervention are severe injuries, which might affect the return to sports and daily activities. We hypothesize that athletic patients will be constrained regarding their sporting activities after surgically treated humeral head fractures. Despite a long rehabilitation program physical activities will change and an avoidance of overhead activities will be noticed.MethodsCase series with 65 Patients, with a minimum follow-up of 24 months participated in this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Whether treated operatively or nonoperatively, the patient may begin finger and wrist range of motion immediately, as well as shoulder pendulums. 19 Patients treated operatively should avoid more than 90° of shoulder abduction and active range of motion for 6 weeks postoperatively. 19 At 6 weeks, whether treated operatively or nonoperatively, a repeat X-ray is taken, and if radiographic healing is present, the patient may begin unrestricted range-of-motion exercises.…”
Section: Upper Extremitymentioning
confidence: 99%
See 1 more Smart Citation
“…Whether treated operatively or nonoperatively, the patient may begin finger and wrist range of motion immediately, as well as shoulder pendulums. 19 Patients treated operatively should avoid more than 90° of shoulder abduction and active range of motion for 6 weeks postoperatively. 19 At 6 weeks, whether treated operatively or nonoperatively, a repeat X-ray is taken, and if radiographic healing is present, the patient may begin unrestricted range-of-motion exercises.…”
Section: Upper Extremitymentioning
confidence: 99%
“… 19 Patients treated operatively should avoid more than 90° of shoulder abduction and active range of motion for 6 weeks postoperatively. 19 At 6 weeks, whether treated operatively or nonoperatively, a repeat X-ray is taken, and if radiographic healing is present, the patient may begin unrestricted range-of-motion exercises. At 10 weeks, patients may begin shoulder strengthening and scapular stabilization.…”
Section: Upper Extremitymentioning
confidence: 99%
“…This question has not been answered even in the adult literature. Ahrens et al found that adults with proximal humerus fractures who were treated with open reduction internal fixation often decreased participation in shoulder-centric sports 22. However, it is reasonable to think that the demands for an anatomic alignment in the adolescent athlete participating in a shoulder-centric sport is greater than average and could be a consideration to raise during a patient and family-oriented preoperative discussion.…”
Section: Outcomes and Functional Demandmentioning
confidence: 99%